Synthesis and efficacy of cinnamon oil formulations and their sustainable release against common house mosquito larvae - Hesham A. Mahran; Shawky M. Aboelhadid; Khaled M. Hassan (Beni-Suef University Journal of Basic and Applied Sciences, 2023)
Abstract Background Control of mosquitoes is considered an essential public health priority. This study was designed to estimate the larvicidal activity of two formulations of Cinnamomum zeylanicum EO for controlling Culex pipiens larvae. Results The prepared formulations were a nanoemulsion of cinnamon (CNE), cinnamon (CN) alone and ordinary cinnamon essential oil mixed with sesame oil (CSO). The cinnamon + sesame oil (CSO) was added as one part cinnamon to 3 parts SO. Different concentrations were prepared and applied following the WHO larvicidal bioassay protocol. Our findings revealed that the LC50 of the CNE form ranged from 85.3 µg/mL to 28.30 µg/mL. The LC50 of SO alone was 1265 µg/mL but when mixed with CNE to form the CSO mixture, this decreased to 159.00 µg/mL. In terms of residual effect, the ordinary form of cinnamon had a residual effect in water for 72 h at a dose of 1000 µg/ml, but this extended to 120 h at the same dose when the CNE form was used. However CSO did not have a residual effect, however. Conclusion The nanoemulsion form significantly improved the efficacy and residual effect of cinnamon against Culex pipiens larvae. Additionally, mixing cinnamon with sesame oil had a synergistic effect. This may assist control strategies against the house mosquito, Culex pipiens.